Understanding the Observed Sex Discrepancy in the Prevalence of Osteoarthritis. Issue 9 (September 2019) - Ferre, Isabella M.; Roof, Mackenzie A.; Anoushiravani, Afshin A.; Wasterlain, Amy S.; Lajam, Claudette M.
Abstract : When stratified by sex and age, there is a greater age-adjusted prevalence of osteoarthritis in women (23.5%) as compared with men (18.1%). The discrepancy between males and females in the prevalence of osteoarthritis is likely multifactorial, being related to hormonal, metabolic, structural, and nutritional differences. Cartilage is lost at a higher rate in women after accounting for confounding variables such as age, body mass index, and bone volume at baseline. Estrogen replacement therapy diminishes the expression of pro-inflammatory cytokines and reduces the prevalence of osteoarthritis in animal models and humans. Much work remains to understand the etiology of the sex gap seen in degenerative joint disease.